ANALISIS PENGARUH RESONANSI MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK PADA PENGGUNA PRODUK SKINCARE MS GLOW DI SURAKARTA - Aulia Muji Setianingrum; Sri Murwanti (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of brand resonance and brand trust on brand loyalty in users of ms glow skincare products in Surakarta. This research method is quantitative research. This study uses primary data is data obtained directly. Primary data is taken through interview techniques using a questionnaire. Meanwhile, the data source in this study is consumers who use Ms Glow Skincare users in Surakarta. In this study, the population used was all users of Ms. Glow Skincare in Surakarta. The sampling technique in this study used non-probability sampling techniques. The number of samples in this study were 150 respondents. In this study using the Partial Least Square (PLS) analysis method with the help of SMARTPLS Software. The results showed that the brand resonance variable has a positive and significant influence on brand loyalty in users of Ms Glow skincare products in Surakarta. Brand trust variables have a positive and significant influence on brand loyalty in users of Ms Glow skincare products in Surakarta. The results of the calculation of f2 show that brand resonance has a large proportion of brand loyalty. While brand trust has a large proportion of brand loyalty. Based on the calculation of R2 value, changes in brand loyalty variables can be explained by changes in brand resonance and brand trust variables. Keywords: Resonance, Trust, Loyalty